Anthropogenic influences on distance traveled and vigilance behavior and stress-related endocrine correlates in free-roaming giraffes - Scheijen, Ciska P. J.; Van der Merwe, Sean; Ganswindt, Andre; Deacon, Francois (MDPI, 2021)
Giraffes are an important tourist attraction, and human presence to wildlife is increasing. This has an impact on an animal’s behavior and its endocrine correlates. Studies on other species show alterations in movement patterns, vigilance, and stress-related hormone levels in the presence of humans. Limited information is available on how anthropogenic activities alter giraffe’s behavior, social structure, and related endocrine parameters. The purpose of this study was to obtain insight into anthropogenic influences on giraffe’s behavior and adrenal activity. We used GPS devices mounted onto giraffes to compare the distance walked in the presence or absence of human observers. We also conducted behavioral observations to assess their vigilance and collected fecal samples to analyze their fecal glucocorticoid metabolite (fGCM) concentrations. Giraffes walked significantly further distances in the presence of humans, but the cumulative time that observers were present decreased the hourly distance walked with an observer present, suggesting that the giraffes were becoming habituated. The number of observers present significantly increased the percentage of time spent on observing an observer as well as the number of unhabituated individuals present in the herd. The percentage of time spent observing a human observer did not decrease with the increase of habituation. Last, fGCM concentrations increased with human presence but decreased when individuals became habituated to human presence. More research is needed to understand the effect of anthropogenic influences in different scenarios (e.g., tourism, vehicles, hunting, etc.).
Keywords: Habituation; Anthropogenic influences; Fecal glucocorticoid metabolites; Stress; Vigilance; Distance traveled